ANALISIS KINERJA REKSADANA SAHAM DAN REKSADANA INDEKS DALAM PENILAIAN TINGKAT EFISIENSI PASAR MODAL INDONESIA - Tona Aurora Lubis; Moeljadi - -; Munawar - Ismail (Wacana Journal of Social and Humanity Studies, 2010)
ABSTRACT The objectives of this research are: first, to know whether LQ-45 Index Fund performs better than the equity mutual fund in Indonesian capital market; second, to measure the level of Indonesian capital efficiency. Results show that the raw performance and risk-adjusted performance of the LQ-45 Index Fund is better than the performance of all equity mutual funds (concurrently). For the investors who wish to invest their capital in equity mutual fund, however, we have found two individual equity mutual fund which perform better than the LQ-45 Index Fund, that is Phinisi Dana Saham and Rencana Cerdas. The result of this research also shows that the excess performance of the LQ-45 Index Fund is smaller than the excess performance of (individual) equity mutual fund. From this result, we may conclude that Indonesian capital market is an inefficient capital market. Â  Keywords: Equity Mutual Fund, Index Fund, Efficiency Market